2013
DOI: 10.1111/eve.12051
|View full text |Cite
|
Sign up to set email alerts
|

An acellular aortic matrix of buffalo origin crosslinked with 1‐ethyl‐3‐3‐dimethylaminopropylcarbodiimide hydrochloride for the repair of inguinal hernia in horses

Abstract: An acellular aortic matrix (AAM) crosslinked with 1-ethyl-3-3-dimethylaminopropylcarbodiimide hydrochloride (EDC) was evaluated for the repair of inguinal hernias in 5 horses. The aorta from buffalo was acellularised using 1% sodium dodecyl sulfate (SDS) and 0.25% trypsin. The AAM was crosslinked with 1% EDC. Under anaesthesia, inguinal hernias were repaired with EDC-crosslinked AAM graft using an inlay graft technique. Blood samples collected on Days 0, 15 and 30 post implantation, were used for SDS polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…36,37 Crosslinking technology has been reported to preserve microstructure. 19 EDC play an important role in these processes. In this study, we optimized previous preparation protocols for APCM and prepared MAPCM with higher transparency, stability and biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Crosslinking technology has been reported to preserve microstructure. 19 EDC play an important role in these processes. In this study, we optimized previous preparation protocols for APCM and prepared MAPCM with higher transparency, stability and biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Decellularized extracellular matrix are complex meshwork of proteins and glycosaminoglycans (GAGs) contained abundant cross-linkable groups, 18 which crosslinked with EDC was proved to improve its biological properties and post-implantation with minimal foreign body reaction, as EDC crosslinking can resist destruction by cell-removing detergents. 19,20 However, thus far, no research has been reported on the effect of EDC on acellular corneal substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the direct use of decellularized tissue in xenotransplantation may cause cross-species responses to structural proteins [ 140 ]. Crosslinking can further reduce this response [ 141 , 142 ]. Kumar et al used BDDGE to crosslink the decellularized swim bladder matrix to explore the effect of crosslinking treatment on wound healing [ 115 ].…”
Section: Applications Of the Swim Bladder In Biomedical Fieldmentioning
confidence: 99%